Predictive Policing in Handling UNRAS Action Rejecting Micro PPKM and Emergency Case Study DKI Jakarta - Mas Iqbal Azizi Zulfian; Muhammad Syaroni Rofii (Budapest International Research and Critics University, 2022)
This research was motivated by the problem of demonstrations against Micro PPKM (Restrictions Towards Community Activities) and Emergency PPKM during the pandemic. This action of refusal is increasingly troubling the community due to the high spread of the COVID-19 virus with public resistance actions against Government policies in preventing the spread of COVID-19 through the implementation of the PPKM. In order to overcome this problem, the most appropriate step is to implement predictive policing as a strategy in overcoming potential threats during the pandemic. In accordance with this background, this research is aimed at analyzing the role of the National Police in handling the Unras action against micro PPKM and the DKI Jakarta case study emergency and analyzing the factors that led to the rise of anarchist demonstrations given the strong impact of non-legal sanctions in micro PPKM and emergency studies. DKI Jakarta case. The results of this study indicate that the role of the National Police in handling the Unras action against micro and emergency PPKM in DKI Jakarta is carried out with precision policing that takes predictive action as an intelligence strategy to prevent various potential threats that exist during the pandemic, so that the PPKM rejection action can be prevented as early as possible. Meanwhile, the factors that led to the rise of anarchic demonstrations, given the strong impact of non-legal sanctions in micro and emergency PPKM in DKI Jakarta, based on the results of an analysis using the theory of relative deprivation, are known to be relative to public understanding and belief regarding the existence of COVID-19 itself. With the belief about COVID-19, preventing rallies against PPKM will be easier to implement, and it is better if the public is not sure about the existence of COVID-19, then preventing demonstrations will be increasingly difficult.